Climate policy 2005 and beyond: Japanese-German impulses. A documentation on the climate policy dialogue and conference between Japan and Germany within the "Germany Year in Japan 2005 - 2006" - Hermann E. Ott; Karin Holl (Wuppertal Institut für Klima, Umwelt, Energie, 2006)
In 2005 two very important milestones of international climate policy were reached: The entry into force of the Kyoto Protocol and the installation of a European wide emissions trading system. In Germany, the publication of the fifth report of the inter-ministerial working group on climate policy was published with an evaluation of climate protection policies. In 2004 the Japanese climate protection policy was fully revised so that Japan will also bring forth important developments in this area. The traditional close cooperation in this area between Japan and Germany, must now result in more concrete projects to keep this dynamic going well into the future. There is much potential to achieve a lot. Within the unique framework of the Germany in Japan Year 2005-2006, the German Ministry for the Environment, the Ministry for Innovation of Northrhine-Westfalia, together with the Institute for Global Environmental Strategies (Japan) and the Wuppertal Institute (Germany) put together a two day event in Tokyo comprising an experts workshop and a one day conference. At the conference, experts and practitioners of the German government, the states, the private sector and environmental organisations from Germany and Europe presented the decisive factors for success as well as the difficulties encountered namely in introducing an eco-tax and the Emissions Trading Scheme. Japanese experts and practitioners reported on Japanese approaches and reviewed the German/European experiences in light of the Japanese situation. At the expert workshop, researchers and decision makers discussed the experiences with policy dialogues and stakeholder involvement. They assessed the transferability of German/European experiences into the Japanese context and the broader inclusion of civil society into the governmental decision making process, that is so say, the opportunities in co-operating with politics, private sector and environmental organisations. This report documents the events and highlights the most outstanding conclusions and ideas for further cooperation in the future. It will begin with the documentation of the conference held on 1 November 2005 followed by the report on the experts workshop held on 31 October 2005. Dr. H. E. Ott will conclude with a short assessment and outlook.
urn:nbn:de:101:1-20091020654
Keywords: 330